Site suitability analysis for landslide monitoring base station using GIS-based multicriteria evaluation technique - Mustafa I.S.; Din N.M.; Ismail A.; Omar R.C.; Khalid N.H.N. (Institute of Electrical and Electronics Engineers Inc., 2023)
Antennas; Electric power transmission; Geographic information systems; Hierarchical systems; Landslides; Maps; Monitoring; Analytical Hierarchy Process; Communication service; Landslide monitoring; Multi-criteria evaluation; Network planning; Pairwise comparison matrices; Power transmission tower; suitability; Base stations